Dynamics of the equatorial ionosphere-thermosphere system as investigated through night airglow techniques - Sobral, J. H. A. (1994)
The dynamics of the nocturnal equatorial F-region has been investigated to a substantial extent in the last few decades by means of airglow diagnostic tools such as photometers, optical imagers and Fabry-Perot interferometric systems. This paper concerns a concise review on those airglow studies.